2023
DOI: 10.1039/d2fo02204d
|View full text |Cite
|
Sign up to set email alerts
|

The association between serum vitamin A and NAFLD among US adults varied in different BMI groups: a cross-sectional study

Abstract: Background and Aims: The association between serum vitamin A (VA) and non-alcoholic fatty liver disease (NAFLD) has not been adequately studied. This study aimed to evaluate the association between them...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Further dose-response studies on antioxidant compounds may be warranted to elucidate the relationship. However, concerning the independent association between intake of vitamin A, vitamin C, vitamin E, and zinc with NAFLD, our results align with several prior studies [52][53][54][55] . Reactive oxygen species (ROS) and lipid peroxidation directly damage hepatocytes by affecting membranes, proteins, and DNA.…”
Section: Discussionsupporting
confidence: 92%
“…Further dose-response studies on antioxidant compounds may be warranted to elucidate the relationship. However, concerning the independent association between intake of vitamin A, vitamin C, vitamin E, and zinc with NAFLD, our results align with several prior studies [52][53][54][55] . Reactive oxygen species (ROS) and lipid peroxidation directly damage hepatocytes by affecting membranes, proteins, and DNA.…”
Section: Discussionsupporting
confidence: 92%
“…Epidemiologic evidence has shown that inadequate vitamin A intake is a significant risk factor for MAFLD and that serum retinol levels are significantly lower in patients with advanced MAFLD [148][149][150]. However, there is also evidence that MAFLD progression may be associated with elevated serum vitamin A levels [151,152]. In addition, vitamin A metabolites, especially retinoic acid, influence the development of MAFLD mainly by affecting the regulatory network of hepatic glucose-lipid metabolism, as well as the interaction with insulin [153,154].…”
Section: Vitamin a Metabolism And Mafldmentioning
confidence: 99%
“…The information from the death certificates was used to derive the Clinical Modification System codes I00-I78 to determine the mortality rate resulting from all-cause mortality and cardiovascular diseases by the International Based on existing information relevant covariates such as age, sex, level of education (less than 9th grade, grades 9-11, high school graduate/GED or equivalent record of formal schooling, partial college or AA degree or above, college graduate or above), BMI, smoking history (never smoked, smoking history), drinking history (less or more than 12 cups/year), aspirin use, family poverty income ratio (PIR:<1.0; 1.0-3.0; >3.0), physical activity, diabetes status, total energy intake, and laboratory measures of blood lipids were included. The energy intake of adults was calculated using the USDA Food and Nutrient Database, available at https://www.ars.usda.gov/nea/bhnrc/ fsrg, which was designed to provide an effective and accurate method to collect intakes for large-scale national surveys (27). Detailed information on dietary vitamin B1 intake and other variables can be accessed at www.cdc.gov/nchs/nhanes/.…”
Section: Variablesmentioning
confidence: 99%